Prevalence and associated factors of nomophobia among undergraduate students of AIIMS Patna - Khumukcham Anupama Devi; Priyanka Elizabeth Thomas (International Journal of Medical Research and Review, 2023)
Introduction: In recent years, the popularity of smartphones has grown to the point that it is unimaginable for individuals to do anything without using one. Nomophobia is the fear of being cut off from one's mobile phone, and it relates to the discomfort, anxiety, tension, uneasiness, and anguish that comes with it. Since the first decade of the twenty-first century, when this social phobia was coined, a growing number of research have investigated and reported the prevalence of this technology-related condition. This study aims to assess the prevalence and associated factors of nomophobia and to determine association of prevalence and associated factors of nomophobia with selected socio demographic variables among undergraduate students of AIIMS Patna. Material and Methods: The research approach here is quantitative approach and the design used here is descriptive. Undergraduate students of AIIMS, Patna are taken as target population in which minimum required sample size was 210 but it was increased to 230 for this study. Data was collected by sending questionnaire via social media. Data analysis was done by using descriptive and inferential statistics. Results: It shows that out of the taken 230 samples, total 229(99.56%) are having nomophobia in which 55(23.913%) are having mild nomophobia, 128(55.652) are having moderate nomophobia, 46(20%) are having severe nomophobia i.e. most of the students are moderately nomophobia. The findings also reveal that there is association of prevalence and associated factors of nomophobia with selected socio demographic variables (Duration of using smartphone per day) with p value 0.000 and the Fisher exact value is 22.169 by using SPSS, the p value for this study is 0.05. Conclusion: The study shows that 99.56% of students are having nomophobia and it is an alarming wake up.